The miR-15/107 Group of MicroRNA Genes: Evolutionary Biology, Cellular Functions, and Roles in Human Diseases - Finnerty, John R.; Wang, Wang-Xia; Hébert, Sébastien S.; Wilfred, Bernard R.; Mao, Guogen; Nelson, Peter T. (Journal of molecular biology, 2010)
The miR-15/107 group of microRNA (miRNA) gene is increasingly appreciated to serve key functions in humans. These miRNAs regulate gene expression involved in cell division, metabolism, stress response, and angiogenesis in vertebrate species. The miR-15/107 group has also been implicated in human cancers, cardiovascular disease and neurodegenerative disease, including Alzheimer's disease. Here we provide an overview of the following: (1) the evolution of miR-15/107 group member genes; (2) the expression levels of miRNAs in mammalian tissues; (3) evidence for overlapping gene-regulatory functions by different miRNAs; (4) the normal biochemical pathways regulated by miR-15/107 group miRNAs; and (5) the roles played by these miRNAs in human diseases. Membership in this group is defined based on sequence similarity near the mature miRNAs' 5′ end: all include the sequence AGCAGC. Phylogeny of this group of miRNAs is incomplete; thus, a definitive taxonomic classification (e.g., designation as a “superfamily”) is currently not possible. While all vertebrates studied to date express miR-15a, miR-15b, miR-16, miR-103, and miR-107, mammals alone are known to express miR-195, miR-424, miR-497, miR-503, and miR-646. Multiple different miRNAs in the miR-15/107 group are expressed at moderate to high levels in human tissues. We present data on the expression of all known miR-15/107 group members in human cerebral cortical gray matter and white matter using new miRNA profiling microarrays. There is extensive overlap in the mRNAs targeted by miR-15/107 group members. We show new data from cultured H4 cancer cells that demonstrate similarities in mRNAs targeted by miR-16 and miR-103 and also support the importance of the mature miRNAs' 5′ seed region in mRNA target recognition. In conclusion, the miR-15/107 group of miRNA genes is a fascinating topic of study for evolutionary biologists, miRNA biochemists, and clinically oriented translational researchers alike.